The L-DOPA/Dopamine Pathway Transgenerationally Regulates Cuticular Melanization in the Pea Aphid Acyrthosiphon pisum - Zhang, Yi; Wang, Xing-Xing; Tian, Hong-Gang; Zhang, Zhan-Feng; Feng, Zhu-Jun; Chen, Zhan-Sheng; Liu, Tong-Xian (Frontiers in Cell and Developmental Biology, 2020)
Maternal phenotypic regulations between different generations of aphid species help aphids to adapt to environmental challenges. The pea aphid Acyrthosiphon pisum has been used as a biological model for studies on phenotypic regulation for adaptation, and its alternative phenotypes are typically and physiologically based on maternal effects. We have observed an artificially induced and host-related maternal effect that may be a new aspect to consider in maternal regulation studies using A. pisum. Marked phenotypic changes in the cuticular melanization of daughter A. pisum were detected via tyrosine hydroxylase knockdown in the mothers during their period of host plants alternations. This phenotypic change was found to be both remarkable and repeatable. We performed several studies to understand its regulation and concluded that it may be controlled via the dopamine pathway. The downregulation and phenotypes observed were verified and described in detail. Additionally, based on histological and immunofluorescence analyses, the phenotypic changes caused by cuticular dysplasia were physiologically detected. Furthermore, we found that this abnormal development could not be reversed after birth. Transcriptome sequencing confirmed that this abnormal development represents a systemic developmental failure with numerous transcriptional changes, and chemical interventions suggested that transgenerational signals were not transferred through the nervous system. Our data show that transgenerational regulation (maternal effect) was responsible for the melanization failure. The developmental signals were received by the embryos from the mother aphids and were retained after birth. APTH RNAi disrupted the phenotypic determination process. We demonstrate that non-neuronal dopamine regulation plays a crucial role in the transgenerational phenotypic regulation of A. pisum. These results enhance our understanding of phenotyping via maternal regulation in aphids.